Validating decarbonisation strategies of climate action plans via digital twins: a Limerick case study - Byrne, Niall; Pierce, Susan; De Donatis, Lorenzo; Kerrigan, Ruth; Buckley, Niall (Frontiers in Sustainable Cities, 2024)
The European Green Deal (EGD) represents the response of the European Union (EU) to the climate crisis and a strategy to mitigate against climate change and the associated environmental degradation. European Climate Law supports the EGD by setting the legally binding target of climate neutrality for the EU on a time horizon of 2050 and mandates that member states develop and implement their own Climate Action Plans (CAP), which are strategic roadmaps outlining steps to reduce greenhouse gas (GHG) emissions and adapt to the impacts of climate change. Within the Irish context, the CAP focuses on six specific sectors, three of which, namely the energy grid, the built environment and transportation are considered in this research. This policy proposes the retrofitting of all residential buildings in the country to a B2 energy performance certificate (EPC), all public transport and 60% of private vehicles electrified and the full decarbonisation of the electrical grid by 2050. This study aims to implement the targets and goals outlined within CAP 2021 in an urban area of Ireland, specifically a historical city centre. The research leverages digital twin technology developed by IES to model the carbon emissions associated with the built environment, while also incorporating GHG emissions associated with transportation and the grid. Furthermore, CAP scenarios are applied systematically and strategically, prioritising building retrofits based on buildings with similar characteristics, typologies and performance. This study has assessed the performance of CAP about two future grid scenarios 1) business as usual and 2) a decarbonised grid. In both scenarios, CAP was not sufficient to achieve the targets set out, resulting in a shortfall of between 25% and 33%. Based on this outcome it may be concluded that any decarbonisation targets specified should be tested and validated before their implementation in policy. Moreover, current state-of-the-art digital twin technologies can facilitate the rapid holistic appraisal of complex multi-sectoral policy at the urban scale, which, depending on data availability, could prove useful in future iterations of CAP at both national and international levels.